Maillard reaction products and amino acid cross-links in liquid infant formula: Effects of UHT treatment and storage. (1st December 2022) - Akıllıoğlu, Halise Gül; Chatterton, Dereck E.W.; Lund, Marianne N.
Graphical abstract: Highlights: Direct and indirect UHT treatment of infant formula was compared. Both UHT treatments had a significant effect on the Maillard reaction. Storage at 40 °C decreased α-dicarbonyl compounds in infant formula. Storage at 40 °C increased furosine and advanced glycation end products. Storage at 40 °C for 6 months caused 20 % blocked lysine in liquid infant formula. Abstract: The formation of Maillard reaction products, including Amadori compounds (determined as furosine), advanced glycation end products (AGEs), α-dicarbonyl and furfural compounds, as well as amino acid cross-links (lysinoalanine and lanthionine) was investigated in direct (DI) and indirect (IN) UHT-treated experimental liquid infant formula (IF) during storage at 40 °C. IN-IF had higher concentrations of all investigated compounds compared to DI-IF and low pasteurized IF. IN UHT treatment induced significantly higher concentrations of α-dicarbonyl compounds (glyoxal, methylglyoxal, 3-deoxyglucosone and 3-deoxygalactosone) compared to DI, which facilitated increased formation of AGEs (N-Ɛ-(carboxymethyl)lysine, methylglyoxal- and glyoxal-derived hydroimidazolones) in unstored IFs. During storage for 6 months, concentrations of furosine and AGEs increased while α-dicarbonyl compounds decreased. Principal component analysis indicated that differences between IN-IF and DI-IF disappeared after 2 months of storage. IN-IF had higher concentrations of lysinoalanine and lanthionine and lower concentrations of available lysine and arginine than DI-IF indicating higher loss of protein quality in IN-IF.